Employment protection and unemployment benefits: on technology adoption and job creation in a matching model - Lommerud, Kjell Erik (2018)
We analyse the effects of different labour-market policies (employment protection, unemployment benefits, and payroll taxes) on job creation and technology choices in a model where firms are matched with workers of different productivity and wages are determined by ex post bargaining. The model is characterized by two intertwined sources of inefficiency, namely a matching externality and a hold-up externality associated with the bargaining strength of workers. The results depend on the relative importance of the two externalities and on worker risk aversion. Flexicurity, meaning low employment protection and generous unemployment insurance, can be optimal if workers are sufficiently risk-averse and the hold-up problem is relatively important.